The Post Crisis Growth in the Self-Employed: Volunteers or Reluctant Recruits? - Andrew Henley (Institute for the Study of Labor (IZA), 2015)
In the UK by late 2014 there were almost 0.75m more self-employed than at the start of the financial crisis in early 2008. This represents over 75% of jobs growth in the UK over the same period. This experience has attracted commentary from independent policy analysts and others, focusing on whether growth has been structural, reflecting changes in the nature of employment and attitudes towards business venturing, or cyclical, reflecting a post-crisis shift towards flexible insecure forms of employment as an alternative to long-term unemployment. Recent commentary has also focused on heterogeneity across UK regions. Longitudinal data covering 2009-2013 from the ESRC Understanding Society survey are used to examine transitions into self-employment, and regression correlation with indicators of labour market conditions (unemployment, earnings) in the area local to the individual. Transitions into self-employment from both previous paid employment and inactivity found to be are negatively correlated with lagged local unemployment rates and positively correlated with lagged lower quartile earnings in the local area. These correlation patterns, although varying in size, hold for men and women, and are robust to controlling for individual characteristics. This suggests that local pull factors are far more significant in driving transitions into self-employment, and explains why business formation rates are higher, post-2008, in more advantaged UK areas. Self-employed business ownership does not appear to a significant alternative to unemployment for those where of paid employment demand is weak. Entrepreneurial activity prospers were wages are higher and unemployment lower.
Keywords: J21; M13; R23; 330; self-employment; local unemployment; local earnings; longitudinal analysis